“THE IMPORTANCE OF DRAWING IN ENHANCING STUDENTS’ CREATIVITY AND VISUAL SKILLS IN ART EDUCATION” - Rustamov Axtam Muxtorovich (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Abstract: This article investigates the importance of drawing in enhancing students’ creativity, visual skills, and cultural awareness in art education. It explores how structured drawing activities improve technical proficiency, creative thinking, and the integration of traditional and national motifs. The study emphasizes that drawing not only develops artistic competencies but also fosters cultural appreciation and reflective learning.